miR-199a-5p Relieves Obstructive Sleep Apnea Syndrome-Related Hypertension by Targeting HIF-1α - Chunyan Guo; Minghui Zhang; Wei Su; Min Xu; Shumei Zhao (Journal of Immunology Research)
Introduction. Obstructive sleep apnea syndrome (OSAS) is related to hypertension. Vascular remodeling is both the pathogenesis and the structural change basis of OSAS-related hypertension. Exploring miRNA functioning in OSAS-related hypertension may offer novel diagnostic and therapeutic targets for controlling hypertension-associated cardiovascular diseases. However, the role of miR-199a-5p in OSAS-related hypertension has not been demonstrated yet. Methods. In this study, we investigated the role of miR-199a-5p and HIF-1α in OSAS-related hypertension by performing in vitro cell experiments and in vivo animal experiments. Rat aortic smooth muscle cells (A7r5) were cultured under hypoxia as an in vitro model. To establish the animal model of OSAS-related hypertension, the rats were under exposure to chronic intermittent hypoxia (CIH) in a hypoxic instrument. The rats were randomly grouped into normal, CIH, CIH+NC, and CIH+miR-199a-5p. Results. By establishing an animal model, we found decreased miR-199a-5p expression and increased HIF-1α expression in OSAS with hypertension. The overexpressed miR-199a-5p could reduce systolic blood pressure and relieve oxidase stress and inflammation. miR-199a-5p treatment could overturn the upregulation of HIF-1α and TGF-β1 and downregulation of α-SMA. Overexpressed miR-199a-5p might attenuate vascular remodeling through HIF-1α downregulation. miR-199a-5p/HIF-1α may inhibit proliferation of vascular smooth muscle cells under hypoxia. Conclusion. miR-199a-5p may relieve OSAS-related hypertension by targeting HIF-1α and be a novel potential therapeutic target.